WHAT IS THE ROLE OF KINESIOPHOBIA AND CATASTROPHIZING IN PHYSIOTHERAPISTS WITH LOW BACK PAIN DURING MANUAL HANDLING OF PATIENTS? - İrem Huzmeli; Nihan KATAYIFÇI; Yusuf Ziya ASLAN; Merve Ülkü ALÇI (Romanian Journal of Physical Therapy, 2022)
Introduction: Chronic low back pain (LBP) is one of the leading causes of years of disability worldwide, resulting in a slew of related health issues and a significant financial burden on society. Professional duties cause both acute and cumulative musculoskeletal disorders and pain in physiotherapists (PT). However, very few studies have found the psychological stress caused by this LBP in physiotherapists, especially fear of movement and catastrophizing. Aim: The current study aimed to assess the kinesiophobia and catastrophic effects of LBP caused by manual patient transfers on PT. Material and methods: This cross-sectional study was carried out face-to-face with PT. Patients treated per day, pain severity, number of patients admitted daily, worked years, daily working hours were recorded. The kinesiophobia [The Tampa Kinesiophobia Scale (TKS)], chronic LBP [The Oswestry Low Back Pain Disability (ODI) Index], and catastrophizing (The Pain Catastrophizing Scale) were evaluated. Results: Fifty-six physiotherapists (24 males and 32 females), between the ages of 23 and 50 years were included. PT’s score of ODI was 10(6-16), and TKS was 35.16±5.77. There were low degree positive correlations between LBP and catastrophizing (r:0.307; p:0.021), kinesiophobia (r:0.338; p:0.010), pain intensity (r:0.473; p<0.001) and patients treated per day (r:0.364; p:0.006). Discussion: It was found that LBP was associated with catastrophizing and fear of movement in physiotherapists. In addition, LBP was associated with the number of hospital admissions and pain severity, and the number of patients admitted daily. Therefore, it is necessary to deliver and increase the education programs on work-related biomechanics among PT's. It is recommended that future studies be carried out with a larger sample of physiotherapists.